Equation of state of iron under core conditions of large rocky exoplanets. (June 2018) - Smith, Raymond; Fratanduono, Dayne; Braun, David; Duffy, Thomas; Wicks, June; Celliers, Peter; Ali, Suzanne; Fernandez-Pañella, Amalia; Kraus, Richard; Swift, Damian; Collins, Gilbert; Eggert, Jon
Abstract The recent discovery of thousands of planets outside our Solar System raises fundamental questions about the variety of planetary types and their corresponding interior structures and dynamics. To better understand these objects, there is a strong need to constrain material properties at the extreme pressures found within planetary interiors1, 2 . Here we used high-powered lasers at the National Ignition Facility to ramp compress iron over nanosecond timescales to 1.4 TPa (14 million atmospheres)—a pressure four times higher than for previous static compression data. A Lagrangian sound-speed analysis was used to determine pressure, density and sound speed along a continuous isentropic compression path. Our peak pressures are comparable to those predicted at the centre of a terrestrial-type exoplanet of three to four Earth masses3, representing the first absolute equation of state measurements for iron at such conditions. These results provide an experiment-based mass–radius relationship for a hypothetical pure iron planet that can be used to evaluate plausible compositional space for large, rocky exoplanets. Iron has been ramp compressed to the pressures it would experience in the core of a 3–4 Earth-mass terrestrial exoplanet, providing experimental constraints on the mass–radius relationship for a hypothetical pure iron planet.